Outcome of Heterotopic Pregnancy Following Ovulation Induction by Clomiphene Citrate (Indian Journal of Case Reports, 2020)
Heterotopic pregnancy, though rare is a combined pregnancy in which simultaneous intrauterine and extrauterine pregnancy occur. The estimated incidence is 1 in 30000 following spontaneous pregnancy while it can be as high as 1 % after the use of artificial reproductive techniques. We present a case of 33 year old female who conceived after ovulation induction with clomiphene citrate and came with acute abdominal pain. Her ultrasound was suggestive of 10 weeks live intrauterine pregnancy with ruptured left tubal ectopic. Laparotomy with left salpingectomy was done without affecting intrauterine pregnancy. Pregnancy progressed uneventfully until 37 weeks and a healthy male baby was delivered by caesarean section. So, heterotopic pregnancy must be considered in a patient with lower abdominal pain in early gestation particularly those who conceive after artificial reproductive techniques.